Single‐agent gemcitabine in patients with advanced, pre‐treated angiosarcoma: A multicenter, retrospective study. (15th August 2022) - Watson, Sarah; Verret, Benjamin; Ropert, Stanislas; Adam, Julien; Bahleda, Rastislav; Briand, Sylvain; Cavalcanti, Andrea; Chamseddine, Ali N.; Court, Charles; Fadel, Elie; Faron, Matthieu; Haddag‐Miliani, Leila; et al.
Abstract: Gemcitabine has shown clinical activity against angiosarcoma in small series, alone, or combined with taxanes. We aimed to evaluate its activity as a single‐agent in a larger series of patients with advanced angiosarcoma. We retrospectively reviewed the electronic medical records of consecutive adult patients with advanced angiosarcoma treated with single‐agent gemcitabine at our institutions from January 2010 to January 2021. Response was evaluated according to RECIST 1.1, and toxicity was graded according to NCI‐CTC v5.0. 42 patients were identified. 38 patients (90%) had received prior anthracyclines and weekly paclitaxel, and 9 (21%) had received pazopanib. The best tumor response was partial response (PR) in 16 patients (38%), or stable disease (10 patients, 24%). All 8 patients with cardiac angiosarcoma experienced a PR. Median PFS was 5.4 months (95%CI: 3.1–6.5), and median OS was 9.9 months (95%CI: 6.6–13.4). Single‐agent gemcitabine has clinically meaningful activity in advanced, heavily pre‐treated angiosarcoma. Abstract : We aimed to evaluate the activity of single‐agent gemcitabine in the largest series of 42 patients with advanced angiosarcoma. The best tumor response was partial response (PR) in 16 patients (38%), or stable disease (10 patients, 24%), median PFS was 5.4 months, and median OS was 9.9 months. Single‐agent gemcitabine has clinically meaningful activity in advanced, heavily pre‐treated angiosarcoma.